Makna Leksikal dan Gramatikal dalam Kajian Semantik pada Lirik Lagu "Lihat, Dengar, Rasakan" Karya Sheila On 7 - Bunga Dwi Yuliana; Febi Cahyani; Fatmawati Fatmawati (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2025)
Semantics is a branch of linguistics that studies meaning in language, whether implied in words, phrases, or sentences. In literary works such as songs, the use of language often contains multiple or symbolic meanings that may cause ambiguity for listeners. This becomes problematic when the audience interprets the lyrics differently from the songwriter’s intent. The song "Lihat, Dengar, Rasakan" by Sheila On 7 is an example of lyrics rich in meaning and symbolism, making it an interesting subject for semantic analysis. The aim of this study is to uncover and explain the lexical and grammatical meanings contained within the lyrics so that the message conveyed can be understood more thoroughly and deeply. This research uses a descriptive qualitative method with observation, note-taking, and content analysis techniques. The results show a total of 17 lexical meaning data and 17 grammatical meaning data in the song lyrics. The lexical meanings consist of 10 synonymy data, 4 antonymy data, 2 homonymy data, 4 hyponymy data, 4 polysemy data, 3 ambiguity data, and 2 redundancy data. Meanwhile, the grammatical meanings include 11 affixation data, 2 reduplication data, and 5 composition data. These findings reveal that the lyrics of "Lihat, Dengar, Rasakan" are rich in complex meanings, both lexically and grammatically. The conclusion of this research is that semantic analysis can unveil the deeper layers of meaning within song lyrics, helping listeners grasp the moral message, social critique, and spiritual values hidden behind the poetic language used by the songwriter.